Penerapan Pembelajaran Literasi di SMP Negeri 2 Sitiotio dengan Memanfaatkan Teknologi Informasi - Oktaviandi Bertua Pardede (Mitra prima, 2022)
Literacy learning needs to be experienced by school students. The goal is to optimize students' ability to understand lessons in depth. Junior High School 2 Sitiotio in Samosir regency seems to need this literacy learning experience. The application of literacy is optimized by utilizing information technology to attract students' interest in experiencing the PKM teaching and mentoring process. Based on observations, it appears that learning activities are conducive and dynamic. Teaching through Unpri's Spada and Zenius application shows that there is a new paradigm for students in literacy learning. The mentoring process also shows continuous interaction outside the classroom. The test results showed that there was an increase in student scores before and after literacy learning by 53.3% with a significance of p < 0.05 and Ha was accepted. Thus, the application of literacy can significantly improve student learning outcomes by utilizing information technology.